اتجاهات أساتذة قسم علم النفس بجامعة المسيلة نحو مفاهيم وتطبيقات الذكاء الاصطناعي دراسة ميدانية بقسم علم النفس بجامعة المسيلة - مشتر الوزد; مزاري وهيبة; اشراف: بوضياف نوال (جامعة محمد بوضياف -المسيلة, 2025)
هدفت الدراسة إلى التعرف على طبيعة اتجاهات أساتذة قسم علم النفس نحو مفاهيم وتطبيقات الذكاء الاصطناعي . ولتحقيق أهداف الدراسة اتبعنا المنهج الوصفي باعتباره الأنسب لوصف الظاهرة وجمع المعلومات و متابعتها في الميدان للحصول على بيانات حقيقية، كما قمنا بتتصميم أداة استبيان لمعرفة طبيعة الاتجاهات نحو مفاهيم وتطبيقات الذكاء الاصطناعي، وزعت على عينة تكونت من (48) أستاذا وأستاذة بقسم علم النفس بجامعة المسيلة، وبعد المعالجة الإحصائية للبيانات أظهرت النتائج أن : • وجود اتجاهات إيجابية لأساتذة قسم علم النفس بجامعة المسيلة نحو مفاهيم وتطبيقات الذكاء الاصطناعي • عدم وجود فروق ذات دلالة إحصائية بين أفراد العينة في اتجاهات الأساتذة نحو مفاهيم وتطبيقات الذكاء الاصطناعي تبعا لمتغير الجنس • عدم وجود فروق ذات دلالة إحصائية بين أفراد العينة في اتجاهات الأساتذة نحو مفاهيم وتطبيقات الذكاء الاصطناعي تبعا لمتغير الأقدمية • عدم وجود فروق ذات دلالة إحصائية بين أفراد العينة في اتجاهات الأساتذة نحو مفاهيم وتطبيقات الذكاء الاصطناعي تبعا لمتغير السن الكلمات المفتاحية: الاتجاهات، أساتذة قسم علم النفس، الذكاء الاصطناعي. Abstarct : The study aimed to identify the nature of the attitudes of psychology department professors towards the concepts and applications of artificial intelligence. To achieve the objectives of the study, we followed the descriptive approach as it is the most appropriate to describe the phenomenon, collect information, and follow it up in the field to obtain real data. We also designed a questionnaire tool to know the nature of attitudes towards the concepts and applications of artificial intelligence, and it was distributed to a sample consisting of (48) male and female professors in the Department of Psychology at the University of M’sila. After statistical processing of the data, the results showed that: • There are positive attitudes among professors of the Department of Psychology at the University of M’sila towards the concepts and applications of artificial intelligence. • There are no statistically significant differences among the sample members in the attitudes of professors towards the concepts and applications of artificial intelligence according to the gender variable. • There are no significant differences Statistical significance among the sample members in the attitudes of professors towards the concepts and applications of artificial intelligence according to the variable of seniority • There are no statistically significant differences among the sample members in the attitudes of professors towards the concepts and applications of artificial intelligence according to the variable of age. Keywords: attitudes, psychology department professors, artificial intelligence.